Forms of Constitutional Disobedience Against Final and Binding Decisions of the Constitutional Court - Hoky Yuro Herlambang (Jurnal Mengkaji Indonesia, 2026)
Abstract: Constitutional Court rulings are final and binding, and thus must be obeyed by all state institutions. Indonesian constitutional practice reveals instances of non-compliance with Constitutional Court rulings—manifested through delayed implementation, disregard for the ruling's operative provisions, or the enactment of new norms that contradict the Court's decisions. This situation gives rise to a phenomenon of "constitutional disobedience," which undermines constitutional supremacy, legal certainty, and the effectiveness of the Constitutional Court in its role as the guardian of the constitution. This study aims to analyze the regulation of constitutional disobedience within the Indonesian constitutional system and to examine the urgency of granting the Constitutional Court the authority to issue judicial orders as a mechanism to strengthen the implementation of its rulings. Employing a normative legal research method, this study utilizes statutory, conceptual, and case-based approaches. The findings indicate that the 1945 Constitution of the Republic of Indonesia does not explicitly address constitutional disobedience nor provide enforcement mechanisms to guarantee the implementation of Constitutional Court rulings, particularly those that are non-self-executing. The study concludes that granting the Constitutional Court the authority to issue judicial orders is necessary as a constitutional instrument to bolster constitutional compliance, ensure the effectiveness of the Court's rulings, and uphold constitutional supremacy and the principle of checks and balances within Indonesia's constitutional system Purpose: Knowing to what extent the Constitutional Court's decisions are binding and final for state institutions. Design/Methodology/Approach: This research falls into the category of normative legal research. Legal research conducted by examining library materials or secondary data is referred to as normative legal research or library-based legal research. Findings: To find out the consequences for state institutions that do not implement the Constitutional Court's decisions, thus causing constitutional disobedience or defiance of the constitution. Originality/value: Offering judicial order as a constitutional mechanism to strengthen the implementation of Constitutional Court decisions.